siRNA targeting prohibitins inhibits proliferation and promotes apoptosis of gastric carcinoma cell line SGC7901 in vitro and in vivo - Zhang, Y.; Chen, Y.; Qu, C.; Zhou, M.; Ni, Q.; Xu, L. (Cellular and Molecular Biology, 2014)
In the present study we investigate the effects of small interfering RNA (siRNA)-mediated silencing of prohibitins (Phbs) gene expressions on gastric carcinoma cell proliferation and apoptosis in vitro and in vivo. Firstly, Phbs proteins in five human gastric carcinoma cell lines were evaluated by Western blotting. Then three siRNA sequences targeting Phbs were designed and transfected into the cancer cell line with the highest Phbs protein expressions. The cell proliferation and apoptosis were analyzed by MTT and flow cytometry methods. In vivo, the effects of siRNAs on the proliferation and apoptosis were assayed in xenografted tumors of nude mice. Phbs proteins were expressed highest in gastric carcinoma cell line SGC7901. The cell proliferation significantly decreased upon Phbs silencing. The cell percentage in S phase was significantly lower in Phbs silenced groups, and the apoptotic cell ratio was significantly higher. siRNA targeting Phbs significantly inhibited the growth of the xenografted tumors. Further, Bcl-2 and Bax was respectively downregulated and upregulated after the Phbs silencing in the xenografted tumors. Caspase-3 and caspase-9 activities were significantly enhanced in the Phbs-silenced tumors. In summary, siRNA-mediated silencings of Phbs inhibit proliferation and promotes apoptosis of gastric carcinoma cells SGC7901 in vitro and in vivo, suggesting key roles of Phbs in the development of SGC7901 cell line.